Cataloging Cultural Objects (CCO) - the CCO Commons examples in VRA Core 4 XML - Arnold, Matthias; Dober, Agnes (Universität, 2020)
“Cataloging Cultural Objects - a Guide to Describing Cultural Works and Their Images” (CCO) provides a data content standard for catalogers of cultural heritage. It is a guidebook for how to populate data elements and where to apply controlled vocabulary standards. The guide is further supported by a larger number of examples in text format provided on the CCO Commons webpage. A project of the Heidelberg Research Architecture focused on encoding all CCO Commons examples in machine readable format using the "strict" version of the VRA Core 4 XML metadata schema. The records make use of the multilingual extensions of the VRA Core 4, developed by the HRA. We provide the full XML data set as example for the implementation of VRA Core 4 XML and a use case for its adaptation to multi-lingual and non-Latin script metadata.
Production date: 2018
Gesehen am 03.08.2020
Keywords: Forschungsdaten; Datenbank